Size‐ and Temperature‐Dependent Suppression of Phonon Thermal Conductivity in Carbon Nanotube Thermoelectric Films. (11th October 2020) - Wesenberg, Devin J.; Roos, Michael J.; Avery, Azure D.; Blackburn, Jeffrey L.; Ferguson, Andrew J.; Zink, Barry L.
Abstract: Heat transport in nanoscale carbon materials such as carbon nanotubes and graphene is normally dominated by phonons. Here, measurements of in‐plane thermal conductivity, electrical conductivity, and thermopower are presented from 77–350 K on two films with thickness <100 nm formed from semiconducting single‐walled carbon nanotubes. These measurements are made with silicon–nitride membrane thermal isolation platforms. The two films, formed from disordered networks of tubes with differing tube and bundle size, have very different thermal conductivity. One film matches a simple model of heat conduction assuming constant phonon velocity and mean free path, and 3D Debye heat capacity with a Debye temperature of 770 K. The second film shows a more complicated temperature dependence, with a dramatic drop in a relatively narrow window near 200 K where phonon contributions to thermal conductivity essentially vanish. This causes a corresponding large increase in thermoelectric figure‐of‐merit at the same temperature. A better understanding of this behavior can allow significant improvement in thermoelectric efficiency of these low‐cost earth‐abundant, organic electronic materials. Heat and charge conductivity near room temperature is also presented as a function of doping, which provides further information on the interaction of dopant molecules and phonon transport in disordered nanotube films. Abstract : Micromachined thermal platform measurements show phonon thermal conductivity of carbon nanotube thermoelectric film formed from HiPCO nanotubes drops to nearly zero in a narrow temperature range, driving a dramatic increase in dimensionless thermoelectric figure‐of‐merit ZT at this temperature.